INTERROGATING THE DISCOURSE OF POWER AND ITS RESISTANCE IN NAWAL EL SADAAWI’S GOD DIES BY THE NILE - Issaka, Charity Azumi; Sanka, Cofidence Gbolo; Resque, Elvis (Sanata Dharma University, 2023)
This paper employs Foucault’s theory on Discourse, Power, and Knowledge to highlight the powers shaping the Egyptian woman in God Dies by the Nile. The paper also uses the feminist theory in identifying the ways that the Egyptian woman uses to resist the discourse of power in the narrative. The paper, therefore, focuses on the power dynamics in the novel. Thus questions addressed in this paper include: how the discourses of family, society, and religion are generated in the novel; how patriarchy shapes the discourse of power in the narrative, and the subtle means used by women to resist and play out power in the novel. Using a thematic approach, textual analysis, and the novel as a primary source, the paper discusses patriarchal discourse and power politics. Examining a selection of discourses and how they affect the body of the female help in appreciating the effect of patriarchy on women in the novel. The study concludes that discourse alone does not explain the power dynamics in the novel. Silence, rebellion, female bonding, and the creation of paranoia in the men through silent but open resistance to patriarchy are some of the power dynamics played out in the novel by the female gender.